Cumulative Family Risk and Cyberbullying Among Chinese Adolescents: The Chain Mediating Role of School Connectedness and Cyber Victimization - Gan, Xiong; Li, Hao; Xiang, Guo-xing; Lai, Xin-hua; Jin, Xin; Wang, Pin-yi; Zhu, Cong-shu (Frontiers in Public Health, 2022)
Abundant evidence has demonstrated that cumulative family risk is associated with cyberbullying. However, few studies to date have investigated how cumulative family risk links to cyberbullying. To fill in these gaps, the present study examined the mediating role of school connectedness and cyber victimization in the relation between cumulative family risk and cyberbullying. A sample of 1,804 Chinese adolescents was recruited to complete measures of cumulative family risk, cyberbullying, school connectedness, cyber victimization, and demographic variables through convenience sampling. There were 813 boys and 991 girls, aged from 13 to 18, with an average age of 16 years (SD = 1.71). Correlational analyses and SPSS macro PROCESS (Model 6) were used for major data analysis. Results indicated that cumulative family risk was positively associated with cyberbullying, and this link could be mediated by school connectedness and cyber victimization. The present study identifies the potential underlying mechanism by which cumulative family risk is associated with adolescent cyberbullying, which has important implications for theory and prevention.